Optimization of BUMDes Financial Management in Mandalika SEZ Area through a Website-Based Accounting Application - Muhammad Hasbiallah; Baiq Anggun Hilendri Lestari; Rini Ridhawati (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Including the Mandalika Special Economic Zone (SEZ) as one of the Priority Tourism Destinations (DPP) proves that West Nusa Tenggara Province is one of Indonesia's provinces with a high tourism potential. Through the Tourism Office, the West Nusa Tenggara government hopes that BUMDes in the Mandalika SEZ area can become the leading sector to boost economic growth. BUMDes is a business entity close to the community, so the development of BUMDes will directly impact the development of the community's economy. One of the obstacles faced by BUMDes in the Mandalika SEZ area is a financial management system that needs to be adequately implemented. The purpose of this research is to design a website-based accounting application model that is easy to operate and has features that suit the needs of BUMDes managers so that they can improve the quality of their financial management. The research method used in this study is a qualitative method with Focus Group Discussion (FGD) data sources and interview results. The results of this study are a website-based accounting application model design that is easy to operate and has features that meet BUMDes managers' needs.